Opaque governance, special purpose vehicles, and the preacher's waiver - Rodolfo Apreda (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2012)
This paper argues that special purpose vehicles, SPVs, are two-edged financial constructs whose bad edge consists in conveying opaque governance, whereas its good one amounts to interesting financial engineering. Firstly, the notion of opaque governance is highlighted, to focus next on SPVs and their governance. Afterwards, the paper delves into collateralized debt obligations and their facilitators, the offshore locations. Last, the failing role of some regulators and gatekeepers is emphasized with the purpose of setting up new measures to prevent them from claiming the Preacher's waiver.
Keywords: G34; G15; G21; G24; 330; opaque governance; special purpose vehicles; collateralized debt obligations; offshore locations; gatekeepers; regulators